Mechanically evoked tinnitus after cochlear implantation with preservation of residual hearing. (2nd November 2022) - Vankatova, Lenka; Hsieh, Julien Wen; Daskalou, Dimitrios; Senn, Pascal
Abstract : In the recent past, inclusion criteria for cochlear implant surgery expanded to patients with ever more residual acoustic hearing in the low frequencies. By applying the meticulous hearing preservation surgical strategy and specifically designed atraumatic electrode arrays, residual hearing can be preserved to a meaningful extent in a large majority of patients. In this paper, we describe two female patients suffering from mechanically evoked tinnitus after hearing preservation cochlear implantation surgery with MEDEL flex electrodes. The occurrence of audible perceptions through mechanical stimulation in the region of the external ear is believed to be due to the direct transmission of movements via the electrode array to the basilar membrane of the inner ear. In both cases, the mechanically evoked tinnitus led to revision surgery with immobilization of the array in the mastoid cavity. Despite eliminating the tinnitus, the revision surgery led to a loss of residual hearing in one patient, whereas the relatively poor residual hearing in the other revision case remained unchanged. The presence of mechanically evoked tinnitus seems to be associated with increased fragility of inner ear structures and hearing function, possibly due to direct mechanical contact of the electrode array with the basilar membrane. Consequently, the electrode array needs to be carefully immobilized in the mastoid cavity at a distance from soft tissue to prevent mechanical damage of inner ear structures, particularly in female patients with fine muscular tissue.